Knowledge and skills in information and communication technology (ICT) of academic librarians in Pampanga an assessment - Santos, Rosalyn B.; Faderon, Rosalie B.; Castillo, Africa R. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2006)
The primary objective of the study was to find out the depth of competency in the use of ICT among academic librarians in their present jobs. The study used the descriptive method of research. The questionnaire was used as the primary tool in gathering data along with ocular inspections and personal Interviews.
Questionnaires were personally retrieved from respondents. Data gathered were organized into frequency and percentage distributions.
Forty-eight (48) academic librarians, twelve (12) of whom were holding supervisory positions, were the respondents of the study. Major findings revealed that academic librarians in Pampanga were competent in terms of general desktop skills, general application skills, disk/file management skills, word processing skills, spreadsheets skills, e-mail skills, and using the internet. Conversely, they have low levels of competence in computer hardware and basic troubleshooting, using databases and using presentation packages. Results further showed the need for further training on the use of databases, computer hardware and basic troubleshooting, and use of presentation software, disk/file management skills and use of spreadsheets as given by respondent librarians. Head librarians likewise think that librarians need ICT training mainly on the above-mentioned skills. Training on networking and use of other operating systems aside from Windows such as Linux have also been suggested.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Academic librarians -- Training of -- Philippines -- Pampanga; Library education -- Philippines -- Pampanga